Bacterial and Antibiotic Sensitivity Patterns in Patient Urine after Percutaneous Nephrostomy - Steven Steven; Ferry Safriadi (Majalah Kedokteran Bandung, 2021)
Percutaneous nephrostomy (PN) is a urine diversion procedure using a tube, stent, or catheter. Knowledge of bacterial sensitivity to antibiotics can guide the establishment of an appropriate and safe treatment to reduce the incidence of percutaneous nephrostomy-related infection (PNCI). The purpose of this study was to determine the suitability of antibiotics medication based on the results of bacterial culture and bacterial sensitivity test. This study was a retrospective descriptive observational study on medical records of patient diagnosed with obstructive uropathy who underwent PN in the period January 2017 to December 2019. A total of 20 bacterial isolates were classified as gram-positive bacteria isolates (16.53%) and 101 isolates presented gram-negative bacteria (83.47%). The most frequent gram-negative bacteria identified in these isolates were E. coli (n=42), Pseudomonas aeruginosa (n=22), and Klebsiella pneumonia (n=20). Meanwhile, Staphylococcus aureus was seen in ten isolates with gram-positive bacteria. Vancomycin antibiotics had the best sensitivity to gram-positive bacteria based on the antibiotic sensitivity tests. On the other hand, meropenem and amikacin had the best sensitivity to gram-negative bacteria (83.2%). This study showed that the most common bacteria identified from nephrostomy patients is E. coli with meropenem and amikacin as the most sensitive antibiotic for these patients. Thus, antibiotic therapy before and after PN procedure should be considered wisely to prevent resistant PNCI.